The Levels and Bactericidal Capacity of Antibodies Directed against the UspA1 and UspA2 Outer Membrane Proteins of Moraxella (Branhamella) catarrhalis in Adults and Children - Chen, Dexiang (American Society for Microbiology, 1999)
The UspA1 and UspA2 proteins from Moraxella catarrhalis share antigenic epitopes and are promising vaccine candidates. In this study, the levels and bactericidal activities of antibodies in sera from healthy adults and children toward UspA1 and UspA2 from the O35E strain were measured. Human sera contained antibodies to both proteins, and the levels of immunoglobulin G (IgG) antibodies were age dependent. Adult sera had significantly higher titers of IgG than child sera (P < 0.01). The IgG3 titers to the UspA proteins were higher than the IgG1 titers in the adults’ sera, while the IgG1 titers were higher than the IgG3 titers in the children’s sera (P < 0.05). The IgG antibodies in the sera from 2-month-old children appeared to be maternally derived, since the mean titer was significantly higher than that in sera from 6- to 7-month-old children (P < 0.05). Serum IgA antibodies to both UspA1 and UspA2 were low during the first 7 months of age but thereafter gradually increased along with the IgG titers. Analysis of sera absorbed with UspA1 or UspA2 showed that the antibodies to UspA1 and UspA2 were cross-reactive with each other and associated with serum bactericidal activity. Examination of affinity-purified human antibodies confirmed that naturally acquired antibodies to UspA1 and UspA2 were bactericidal and cross-reactive. These results support using UspA1 and UspA2 in a vaccine to prevent M. catarrhalis infections.